2022
DOI: 10.3390/molecules27062014
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil Traceability Studies Using Inorganic and Isotopic Signatures: A Review

Abstract: The olive oil industry is subject to significant fraudulent practices that can lead to serious economic implications and even affect consumer health. Therefore, many analytical strategies have been developed for olive oil’s geographic authentication, including multi-elemental and isotopic analyses. In the first part of this review, the range of multi-elemental concentrations recorded in olive oil from the main olive oil-producing countries is discussed. The compiled data from the literature indicates that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 106 publications
0
10
0
Order By: Relevance
“…Also, Pb has four stable isotopes, and it comes from the soil, but its natural concentration in plants is low. The Pb accumulation in plants was strictly related to a contaminated environment due to anthropogenic activity, such as mining, industry, coal-burning and gasoline (Nasr et al, 2022). All these factors enable Sr and Pb isotopes as suitable markers of specific geographical situations.…”
Section: Isotopes Ratiomentioning
confidence: 99%
“…Also, Pb has four stable isotopes, and it comes from the soil, but its natural concentration in plants is low. The Pb accumulation in plants was strictly related to a contaminated environment due to anthropogenic activity, such as mining, industry, coal-burning and gasoline (Nasr et al, 2022). All these factors enable Sr and Pb isotopes as suitable markers of specific geographical situations.…”
Section: Isotopes Ratiomentioning
confidence: 99%
“…Nevertheless, the suitable regions for olive cultivation in China still have considerably distinct weather and soil conditions that are similar to those of the Mediterranean Basin (e.g., local olive trees experience more rainfall and less solar radiation during the flowering and fruiting stages). Consequently, VOO from the same cultivar produced under different geographical and climatic parameters may differ in yield per acre and chemical character/composition (Nasr et al., 2022; Rodrigues et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the isotopic fractionation of the elements for the geographical discrimination of olive oil is highly correlated with the geographical and climatic parameters (Nasr et al, 2022). NMR technique has many advantages such as; high reproducibility, profitable use for fingerprint analysis, fast measurement, minimal sample preparation, long-term sample storage, and suitable for untargeted and targeted analysis and many components and quality characteristics can be simultaneously analyzed in a few minutes at the same time (Emwas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%